2013
DOI: 10.1242/dev.102731
|View full text |Cite
|
Sign up to set email alerts
|

Specification of dopaminergic subsets involves interplay of En1 and Pitx3

Abstract: On p. 3374, a section of the microarray analysis text should read as follows: Analysis was performed as described (Roepman et al., 2005). Data were analyzed using ANOVA (R version 2.2.1/MAANOVA version 0.98-7) (Wu et al., 2003). Genes with P<0.05 after false discovery rate correction were considered to be significantly changed. Mouse Whole Genome Gene Expression Microarrays V1 (Agilent Technologies, Belgium) containing mouse 60-mer probes were used and data have been deposited in ArrayExpress under accession n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
66
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(70 citation statements)
references
References 0 publications
2
66
0
Order By: Relevance
“…Of several investigated MbDN markers only Nr4a2 expression is maintained in both areas (Fig. 2) [105]. The absence of most MbDN markers is reminiscent of the phenotype observed when FGF signaling is ablated in the midbrain, suggesting that EN1 might function downstream of FGF signaling in the specification of midbrain identity in MbDNs [96].…”
Section: Signaling Pathwaysmentioning
confidence: 89%
“…Of several investigated MbDN markers only Nr4a2 expression is maintained in both areas (Fig. 2) [105]. The absence of most MbDN markers is reminiscent of the phenotype observed when FGF signaling is ablated in the midbrain, suggesting that EN1 might function downstream of FGF signaling in the specification of midbrain identity in MbDNs [96].…”
Section: Signaling Pathwaysmentioning
confidence: 89%
“…The PBX family of transcription factors is composed of four members in mammals (PBX1-4) (Moens & Selleri, 2006;Longobardi et al, 2013). Expression of Pbx genes has been detected in both the mouse and human midbrain as well as mDAn (Thompson et al, 2006;Yin et al, 2009;Ganat et al, 2012;Sgado et al, 2012;Veenvliet et al, 2013). However, to date only a very mild mDAn axon guidance phenotype has been described in Pbx1 null embryos (Sgado et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that En1/2 survival activity on mDA neurons in these mice could be mediated through both, the activation of Erk1/2 MAPK survival pathway and suppression of the pro-apoptotic activity of the pro-neurotrophin receptor p75NTR [10]. Finally, a recent study also analyzed En1À/À mice, which are viable on a C57BL/6 background, and reported a much more rapid and pronounced postnatal loss of mDA neurons [35]. All these observations support the idea that En1/2 continues to be required for the survival and/or maintenance of a subset of mDA neurons during adulthood.…”
Section: Progressive Loss Of Mda Neurons In En1+/à Micementioning
confidence: 99%